A novel study on the mechanisms of drug release in PLGA-mPEG microspheres with fluorescent drug. Issue 9 (12th June 2016) - Shi, Chen; Feng, Shuibin; Liu, Ping; Liu, Xianzhe; Feng, Xiaobo; Fu, Dehao
Abstract: The purpose of this research was to proof the microspheres release mechanism by a novel method-detecting and comparing the drugs fluorescent changes on the microspheres surface. Fluorescein sodium (FS, 0.4 kDa) and fluorescein isothiocyanate-bovine serum albumin (FITC-BSA, 66.8 kDa) were employed as model drugs. FS and FITC-BSA were encapsulated into PLGA-mPEG microspheres through double emulsion evaporation method, and the drug-loaded microspheres in vitro degradation and release behaviors were evaluated by scanning electron microscope, gel permeation chromatography, confocal laser scanning microscopy (CLSM), BCA assay kit, and UV–vis spectrophotometry. FS-loaded microspheres revealed a severe initial burst release, followed by a sustained release, and we could observe a bright fluorescent on the microspheres surface during the early release period under the CLSM. The bright fluorescent gradually faded out in the later period as only 1 2% FS was remained after 14 days release. FITC-BSA-loaded microspheres revealed a typical tri-phase release profile, and we observed a weak fluorescent on the microspheres surface after the initial burst release, and the fluorescent came bright again after an obvious erosion appeared on the microspheres surface. In the later release stage, the fluorescent gradually faded out as the fast release of FITC-BSA.